Personality traits affect young people's intention to study - Frauke Peter; Johanna Storck (DIW Economic Bulletin, 2014)
Although in recent years the number of new students has been growing constantly, socio-economic differences remain an issue in the transition from school to college: those eligible for higher education whose parents do not have a college degree are less likely to take up higher education than their peers from academic parental homes. This means that they may not be fully utilizing their educational potential. A study by DIW Berlin examines how personality traits for both groups play a role in creating the intention to go to college. The present study is based on data from the Socio-Economic Panel (SOEP) study and shows that personality traits do indeed affect the intention to study of adolescents aged 17. The probability of taking up tertiary education increases among students taking their Abitur (school-leaving certificate that serves as a qualification for German university entrance) when they are more open to new experiences or are less anxious and insecure. This applies to young people with the same academic performance and in particular to students from non-academic parental homes.
Keywords: I21; I24; J24; 330; intention to study; personality traits